Symptomatic aggravation after corticosteroid pulse therapy in definite sporadic Creutzfeldt-Jakob disease with the feature of Hashimoto’s encephalopathy - Jang, Jae-Won (BioMed Central, 2014)
BACKGROUND: Creutzfeldt-Jakob disease and Hashimoto’s encephalopathy often show similar clinical presentation. Among Creutzfeldt-Jakob disease mimics, Hashimoto’s encephalopathy is particularly important as it is treatable with corticosteroids. Thus, in cases of middle-aged woman diagnosed with probable Creutzfeldt-Jakob disease and who exhibit high titers of antithyroid antibodies, corticosteroid pulse therapy is typically performed with expectations of near complete recovery from Hashimoto’s encephalopathy. Herein, we provide the first case report that exhibited a negative effect of corticosteroid pulse therapy for a patient with Creutzfeldt-Jakob disease with features of Hashimoto’s encephalopathy. CASE PRESENTATION: We report a case of 59-year-old Asian woman with blurred vision, dysarthria, myoclonus, and rapidly progressive dementia. Cerebrospinal fluid showed 14-3-3 protein positive. Electroencephalogram showed periodic sharp waves (1.5 Hz) at the bilateral frontal or occipital areas. Magnetic resonance imaging showed high signal intensities at the bilateral cerebral cortex, caudate nucleus, and putamen. The patient was diagnosed with probable Creutzfeldt-Jakob disease. However, serum analysis showed a high titer of antithyroid antibodies. We started corticosteroid pulse therapy with subsequent aggravation of seizure activity including generalized myoclonus, epilepsia parialis continua, and ballistic dyskinesia, which was effectively treated with clonazepam. CONCLUSION: We provide evidence of a case of Creutzfeldt-Jakob disease that exhibited clinical deterioration after corticosteroid therapy. Although histopathological confirmation with brain biopsy is not easily available in Creutzfeldt-Jakob disease patients, selective initiation of corticosteroid pulse therapy should be considered in cases of uncertain diagnosis for differentiation with Hashimoto’s encephalopathy.